The effect of interfacial zone due to nanoparticle-surfactant interaction on dielectric properties of vegetable oil based nanofluids - Farade, Rizwan A.; Abdul Wahab, Noor Izzri; Mansour, Diaa Eldin A.; Azis, Norhafiz; Jasni, Jasronita; Veerasamy, Veerapandiyan; Vinayagam, Arangarajan; Kotiyal, Bandanawaz M.; Yunus Khan, T. M. (Institute of Electrical and Electronics Engineers, 2021)
Nanoparticles are generally anti-lipophilic and have a tendency to aggregate when they are embedded in nanofluids. Thus, surfactants have a major role in achieving long term dispersion stability of nanofluids through surface modification of nanoparticles. However, the surfactant changes the structure of the interfacial zone around nanoparticles and can have a crucial impact on the dielectric properties of dielectric nanofluids. Accordingly, this paper aims to clarify the role of interfacial zone on dielectric properties of vegetable oil based Al 2 O 3 nanofluids including relative permittivity, dissipation factor, and AC breakdown voltage. Moreover, a polarization model of nanofluids was proposed to calculate their relative permittivity considering surfactant effect. Different filler levels ranging from 0.01 wt% to 0.05 wt% were used and various temperature ranges were considered to validate the proposed model. Relative permittivity calculated from the proposed model was almost in line with experimental results. Proposed model depicted that surfactant contributes for orientational polarization of nanoparticles in the relative permittivity calculation. So, improvement in the relative permittivity of dielectric nanofluids has been attained from 0.01 wt% to 0.05 wt% of Al 2 O 3 nanoparticles due to both internal and orientational polarization of nanoparticles. Regarding dissipation factor of prepared nanofluids, it decreased against the weight percentage of nanoparticles, while the mean AC breakdown voltage increased against the weight percentage. All these effects were discussed considering the structure of interfacial zone and its impact on the alignment of oil chains and the energy loss of electrons.